Mutagenicity and clastogenicity of gas stove emissions in bacterial and plant tests - Monarca, S.; Zanardini, A.; Feretti, D.; Falistocco, E.; Antonelli, P.; Resola, S.; Moretti, M.; Villarini, M.; Nardi, G. (Environmental and molecular mutagenesis, 1998)
The aim of this research was to study the gaseous and particulate emissions of genotoxic substances during cooking with two types of methane stoves (a new one and an old one). The particulates were sampled both with a cascade impactor air sampler and an impinger with ice trap and analyzed by two bacterial mutagenicity tests (Ames and Kado tests) and by HPLC for polycyclic aromatic hydrocarbons (PAH). Gaseous emissions were studied in situ using the Ames test, a clastogenicity plant test (Tradescantia‐micronucleus test), and in an automated system for chemical analyses. Clear indirect mutagenicity was found only with the Kado test (TA98‐S9) in extracts of particulates emitted from the old methane stove and collected with the impinger. Similar mutagenicity (TA98+S9) was also found for the finest fraction of particulates (<0.5 um) collected from both stoves. Gaseous emissions of both stoves caused clastogenicity in the in situ experiments with the Tradescantia‐micronucleus test. The physico‐chemical analyses of the emissions showed also the presence of very fine particulates and trace amounts of PAH. The exposure of these genotoxins could be particularly important for occupationally exposed individuals in homes and businesses and for susceptible subjects living indoors for long periods (infants, children, the sick, and the elderly). Environ. Mol. Mutagen. 31:402–408, 1998. © 1998 Wiley‐Liss, Inc.